Morphogenetic divergence in T. aman rice (Oryza sativa L.) - Rahman, MM; Rasul, MG; Bashar, MK; Mian, MAK; Haque, MM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 67